PENGEMBANGAN INSTRUMEN PENILAIAN KOGNITIF DAN AFEKTIF BERBASIS KURIKULUM KKNI PADA MATA KULIAH MATEMATIKA DISKRIT UNTUK MAHASISWA PROGRAM STUDI TADRIS/PENDIDIKAN MATEMATIKA IAIN PADANGSIDIMPUAN - Amir, Almira; Nasution, Mariam (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2022)
The demand for analytical, synthesis and evaluation skills applies to all students, especially in the Tadris/Mathematics Education study program, FTIK IAIN Padangsidimpuan. Students are educated to become prospective mathematics teachers so that high cognitive abilities are needed. The Tadris/Mathematics Education study program has implemented the 2015 KKNI curriculum. For the Discrete Mathematics course, it has not yet developed learning tools using the KKNI curriculum.The purpose of the study was to determine the validity, practicality, and effectiveness of cognitive and affective assessment tools based on the IQF curriculum for the Discrete Mathematics course. The research was carried out in the tadris/Mathematics education study program in semester 4 T.A. 2019/2020 which consists of 2 classes, namely TMM-1 and TMM-2, each of which amounts to 24 people and 33 people. The development model used in this study is a 4-D model, namely defining, designing, developing and disseminating.The results of the research and discussion showed that the cognitive and affective assessment tools based on the KKNI curriculum for the Discrete Mathematics course developed were categorized as very valid at 3.91 or 97.9% for cognitive assessments and 3.71 or 92.85% for affective assessments. Cognitive and affective assessment tools based on the IQF curriculum in the Discrete Mathematics course for students of the tadris/Mathematics education study program developed were categorized as very practical with the final score percentages of 81.56% and 89.93%, respectively. Practicality can be seen from students using cognitive and affective assessment tools.